Morphology of Maxillary Labial Frenum in Chepang Community of Chitwan - Chaulagain, Rajib; Khanal, Nikita; Singh, Ashutosh Kumar (Journal of Nepal Health Research Council, 2021)
Background: Labial frenum is a fold of mucous membrane whose function is to attach lips and cheek to the alveolar mucosa, gingiva and underlying periosteum. The maxillary labial frenum has lot of variation in shape, size location. This study was aimed to assess the variation of maxillary labial frenum in the indigenous Chepang community of Nepal.Methods: A descriptive cross-sectional study was conducted among the Chepang community at Madi municipality in Chitwan, Nepal. The clinical examination was done by distending the upper lip upward for viewing. The obtained data was classified according to Mirko and Sewerin classification. Data was entered into Statistical Package for the Social Sciences version 16 and descriptive statistics was performed.Results: All the Chepang participants 102 (100 %) had mucosal type of maxillary frenum. Among the variations normal frenum was mostly present 74 (72.5%). This type was mostly present in male participants 44 (43.1%). Apart from this frenum with nodules and appendix was also observed.Conclusions: The mucosal type of frenal attachment was prevalent in Chepang Community and normal frenum was the most common type of frenal morphology. Keywords: Chepang community; maxillary labial frenum; mucosal